Development of novel distance relay scheme to prevent false tripping during power swing / Nor Zulaily Mohamad - Mohamad, Nor Zulaily (Institute of Graduate Studies, UiTM, 2017)
Contingencies in a power system such as a sudden change of load, a power system fault, or a trip of large generation unit, may cause instability issue in which eventually may lead to the power swing phenomenon. During a power swing, the distance relay is prone to operate falsely and, as a result, this false operation has often contributed to major power outages. Therefore, there is a need for development of a comprehensive protection scheme to improve sensitivity of the distance relay operation during power swing. The objectives of the research are to develop new intelligent schemes for preventing false relay operation during power swing. The initial work carried out in this study focuses on developing a new detection scheme that able to detect a fault that occurs during power swing. Another new detection scheme is also developed in this study for identifying the type of power swing. These two detection schemes are conceptually based on S-Transform feature extraction of the distance relay input signal. Moreover, a new adaptive distance protection algorithm is also developed to block the false tripping operation during power swing and unblock the operation if a fault occurs during power swing.